PELAKSANAAN GOOD GOVERNANCE DAN PENERAPAN SISKEUDES BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 20 TAHUN 2018 TENTANG PENGELOLAAN KEUANGAN DESA (Studi Kasus pada Desa di Kecamatan Bengkalis, Kabupaten Bengkalis, Provinsi Riau) - Saputra Ardian; Agusti Restu; Oktari Vera (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
Village finance is a strategic matter for the village as well as for government above the village, namely the district. The importance of village finance is emphasized by the existence of Law on Village Number 6 of 2014 and Permendagri No. 20 of 2018 concerning Village Financial Management. In the implementation and management of village finance, it must be managed based on transparent, accountable, participatory principles and carried out in an orderly and disciplined budget. This study used qualitative research methods to obtain facts about the financial management process in Senggoro, Kelapapati and Wonosari villages. The unit of analysis in this research is the Government of Senggoro Village, Kelapapati Village and Wonosari Village. The data collection techniques used were in-depth interviews, observation and documentation to complement the data in this study. Senggoro Village, Kelapapati Village and Wonosari Village have been participatory, involving the head of the BPD and community elements in the formulation of financial plans and village development. In the implementation and administration in Senggoro Village, Kelapapati Village and Wonosari Village have followed the Permendagri No. 20 of 2018 concerning Village Financial Management, so that the flow of implementation is good. Likewise, in the reporting and accountability of the Senggoro and Wonosari Village Governments, it has been transparent to the community regarding the realization of village finances by disseminating financial reports to elements of the community. Meanwhile, Kelapapati Village is considered to be lacking in socializing transparency regarding the realization of village finances. In implementing the Siskeudes application, the Government of Senggoro Village, Kelapapati Village and Wonosari Village have been maximized and greatly helped by the Siskeudes application in village financial management.Keywords: Accountability, Transparency, Participation, Siskeudes, Village Finance Management, Village Government